Desvendando os mitos do bom professor: um estudo com professores da educação básica - Pereira, Ana Lúcia (2009)
In order to address the problem Does the myths of the good teacher permeate the positioning of teachers in respect to the teaching practice? , this work aimed to understand the placement of teachers in basic education against the four myths of good teacher: 1) The good teacher is always ca4lm and balanced, invariably can control yourself, never loses his composure or show strong emotions; 2) The good teacher accepts all students from the same way, having no favorites; 3) The good teacher can create an environment that, while remaining quiet and calm, promote an exciting learning, stimulating and free; 4) the good teacher knows all the answers, having a higher wisdom to the students. Study participants were eleven teachers of basic education working in a private school located in the southern city of Sao Paulo. The option for a qualitative approach and the critical incidents as a resource for production information was chosen. Understanding critical incidents as "detailed description of a fact and the situation that gave rise to it in order to provide a basis for the participant to give an opinion, trial or decision making", were drawn up four incidents concerning in the four myths surveyed for presentation to the teachers. Based on their responses, were proposed categories of analysis, from which (we tried) to identify clues to the accession of the participants in each myth analyzed. Data analysis was conducted in light of the theoretical framework of Carl Rogers and Thomas Gordon. The results showed great support by the participants to the four myths surveyed, suggesting the importance of the issue to be considered in training programs for teachers